Female genital actinomycosis: a review of 24 cases - Kubelka-Sabit, Katerina; Prodanova, Irina; Yashar, Genghis; Zografski, George; Basheska, Neli (Springer, 2006)
Objectives: The aim of this retrospective study was to present the clinical characteristics of the patients with female genital actinomycosis in correlation with the histopathological findings. Actinomycosis is a relatively rare chronic granulomatous inflammatory disease caused by the bacteria Actinomyces israelii, a normal commensal of the gastrointestinal and genital tract. The abdominal form of the disease is rare, however the incidence of the female genital and pelvic actinomycosis is rising, especially among the intrauterine device (IUD) users (8-20%). Methods: According to the computer database at our department, 965 cases of endometritis, 6,313 cases of cervicitis and 584 cases of pelvic inflammatory disease (PID) were diagnosed in a 15-year period (1991-2005). However, only 21 (2.2%) cases of endometrial, 1 (0.02%) cervical actinomycosis and 2 (0.3%) cases of pelvic actinomycosis were identified in this period. Explorative curettage was performed in 21 patients due to prolonged uterine bleeding and extirpation of an IUD was done in 19 of them. One patient had a biopsy taken for a suspicion of cervical neoplasm, consecutively diagnosed as endometrial adenocarcoma. In the PID group, one patient with a previous history of tubal pregnancy underwent a transabdominal biopsy for a paravesical tumor, two weeks after extirpation of an IUD. The last patient had no IUD and was surgically treated with hysterectomy and bilateral adnexectomy for a suspicion of malignant ovarian tumor. The biopsy, curettage and operative materials were formalin-fixed, routinely processed and paraffin-embedded. 4 microns thin sections were cut and slides were stained using standard hematoxylin–eosin staining procedure. Results: The mean age of the patients was 52.3 ranging from 41 to 68. Macroscopically visible sulfur granules were not identified in any of the cases of disease confined to the uterus. However microscopically, in all the 22 biopsy and curettage materials, elements of chronic granulomatous endometritis and/or cervicitis were seen, together with branching filaments of Actinomyces. In the paravesical tumor, abscesses filled with necrotic debris and scattered Actinomyces colonies were found. Macroscopically visible sulfur granules were identified only in the operative material, where a rough necrotic greyish-yellow area was seen on the serosal surface on the left side and posterior wall of the uterine corpus, measuring 4 × 3 cm. A left tubo-ovarian abscess measuring 4 × 3 × 3 cm was also found. On sectioning, several small and large abscesses filled with puss were present. The histological examination confirmed multiple actinomycotic abscesses in the ovary, paraovarian region and the external third of the left lateral uterine wall. Conclusions: Female genital actinomycosis is a rare and obscure granulomatous disease. It is most prevalent in IUD carriers and easily diagnosed when confined to the uterus. However, the pelvic actinomycosis is often misdiagnosed, simulating malignant pelvic or ovarian tumor. Therefore, unnecessary surgical interventions can be avoided with a careful examination of these patients and a timely identification of the disease.
Keywords: female genital tract; Actinomycosis; uterus; IUD; pelvic; histopathology